2020
DOI: 10.1038/s41401-020-0424-4
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing nanomedicine to overcome the immunosuppressive tumor microenvironment

Abstract: Cancer immunotherapy has received extensive attention due to its ability to activate the innate or adaptive immune systems of patients to combat tumors. Despite a few clinical successes, further endeavors are still needed to tackle unresolved issues, including limited response rates, development of resistance, and immune-related toxicities. Accumulating evidence has pinpointed the tumor microenvironment (TME) as one of the major obstacles in cancer immunotherapy due to its detrimental impacts on tumor-infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 211 publications
(288 reference statements)
0
41
0
Order By: Relevance
“…Despite the lack of pathology in our discovery and validation datasets, the sCMRs were enriched for sites showing altered DNAm in syndromes or disorders of sex chromosomes, X-linked loci or chromatin modellers. We also found that a subset of sCMRs had altered DNAm patterns in tumor samples, an effect that may reflect chromosomal abnormalities typical of cancer cells or the microenvironment of tumors ( 86 ). Nevertheless, it remains unknown whether sCMRs underscore sex differences in disease or susceptibility to the environment.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the lack of pathology in our discovery and validation datasets, the sCMRs were enriched for sites showing altered DNAm in syndromes or disorders of sex chromosomes, X-linked loci or chromatin modellers. We also found that a subset of sCMRs had altered DNAm patterns in tumor samples, an effect that may reflect chromosomal abnormalities typical of cancer cells or the microenvironment of tumors ( 86 ). Nevertheless, it remains unknown whether sCMRs underscore sex differences in disease or susceptibility to the environment.…”
Section: Discussionmentioning
confidence: 66%
“…It can be obtained by the secretion of cytokines with the following recruitment of Treg and MDSCs (myeloid-derived suppressor cells), and changes in amino-acids metabolism. Arginine, glutamine, leucine, and tryptophan are among those which are now under investigation and establishment of their function will help to better understand the biology of cancer [6][7][8]. Due to the broad role of each of the listed amino-acids, it is not possible to describe them in detail in one manuscript.…”
Section: Mechanisms Involved In Immune Evasionmentioning
confidence: 99%
“…AMD3100, an antagonist of CXCR4, blocks the signaling of CXCR4 after binding to CXCR4, although cross-reactive to other chemokine receptors as previously reported [15], and thus play an important role in inhibition of tumor growth and metastasis. Emerging evidence demonstrates that the accumulation of immunosuppressive cells in the TME greatly reduce antitumor efficacy of the treatment, making it one of the major obstacles to cancer immunotherapy [16,17]. Immune cells are involved in different periods of tumor progression.…”
Section: Introductionmentioning
confidence: 99%